2015
DOI: 10.1051/epjconf/20159404044
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analysis concerning the behaviour of OL50 steel grade specimens coated with polyurea layer under dynamics loadings

Abstract: Abstract. This study refers to an experimental and numerical evaluation of a polyurea coating layer influence on the dynamic behaviour of OL50 specimens. Mechanical quasi-static and dynamic tensile tests were performed in axial loading conditions, for 2 mm steel plate specimens. Several metallic specimens have been previously coated with 1.5 mm and 3 mm respectively thickness polyurea layer and tested in traction. The findings results indicate that the presence of polyurea changes the loading pattern of metall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Polyurea has been reported as a good candidate for impulsive loading applications since it has been demonstrated that it is intrinsically reinforced by its morphology, consisting of a continuous rubbery soft matrix containing well dispersed nanoscaled hard domains . Recent studies proved that a polyurea coated steel plate could suffer lower deformations than an uncoated one when subjected to impulsive loading . A polyurea nanocomposite could present even more advantages than the neat polyurea.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurea has been reported as a good candidate for impulsive loading applications since it has been demonstrated that it is intrinsically reinforced by its morphology, consisting of a continuous rubbery soft matrix containing well dispersed nanoscaled hard domains . Recent studies proved that a polyurea coated steel plate could suffer lower deformations than an uncoated one when subjected to impulsive loading . A polyurea nanocomposite could present even more advantages than the neat polyurea.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, for a better understanding of materials behavior, during the experimental tests (mechanical testing, ultrasonic testing), different types and configurations of samples and measurement tools have been tested (simple/bilayer/multilayer configurations, force or pressure transducers, videospeed cameras, scanning electron microscopy, computed tomography etc. ), in static, dynamic or impulsive regime, corroborated with numerical simulation, in order to obtain valid outcomes and results that can be extrapolated to large-scale experiments and applications [13,[20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“… Composite structure implementations are structures employed to absorb energy through plastic deformation, limiting the transferred force due to the specific stress-strain relationship of the material. Significant examples are hyperelastic materials [ 9 , 10 ], metal foams [ 11 , 12 , 13 ] and sandwich structures [ 14 ]. Detonation wave deflection: systems that deflect the blast away from the structure they are protecting, such as V-shells [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Composite structure implementations are structures employed to absorb energy through plastic deformation, limiting the transferred force due to the specific stress-strain relationship of the material. Significant examples are hyperelastic materials [ 9 , 10 ], metal foams [ 11 , 12 , 13 ] and sandwich structures [ 14 ].…”
Section: Introductionmentioning
confidence: 99%